What Is It About Humanity That We Can’t Give Away To Intelligent Machines? A European Perspective - Coombs, Crispin; Stacey, Patrick; Kawalek, Peter; Simeonova, Boyka; Becker, Jörg; Bergener, Katrin; Carvalho, João Álvaro; Fantinato, Marcelo; Garmann-Johnsen, Niels F.; Grimme, Christian; Stein, Armin; Trautmann, Heike (International Journal of Information Management)
One of the most significant recent technological developments concerns the development and implementation of ‘intelligent machines’ that draw on recent advances in artificial intelligence (AI) and robotics. However, there are growing tensions between human freedoms and machine controls. This article reports the findings of a workshop that investigated the application of the principles of human freedom throughout intelligent machine development and use. Forty IS researchers from ten different countries discussed four contemporary AI and humanity issues and the most relevant IS domain challenges. This article summarizes their experiences and opinions regarding four AI and humanity themes: Crime & conflict, Jobs, Attention, and Wellbeing. The outcomes of the workshop discussions identify three attributes of humanity that need preservation: a critique of the design and application of AI, and the intelligent machines it can create; human involvement in the loop of intelligent machine decision-making processes; and the ability to interpret and explain intelligent machine decision-making processes. The article provides an agenda for future AI and humanity research.

Towards Feature-Free Automated Algorithm Selection for Single-Objective Continuous Black-Box Optimization - Prager, Raphael Patrick; Vinzent Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (2021 IEEE Symposium Series on Computational Intelligence (SSCI))
We propose a novel method for automated algorithm selection in the domain of single-objective continuous black-box optimization. In contrast to existing methods, we use convolutional neural networks as the selection apparatus which bases its decision on a so-called ‘fitness map’. This fitness map is a 2D representation of a two dimensional search space where different gray scales indicate the quality of found solutions in certain areas. Our devised approach uses a modular CMA-ES framework which offers the option to create the conventional CMA-ES, CMA-ES with the alternate step-size adaptation and many other variants proposed over the years. In total, 4 608 different configurations are possible where most configurations are of complementary nature. In this proof-of-concept work, we consider a subset of 32 possible configurations. The developed method is evaluated against an excerpt of BBOB functions and its performance is compared against baselines that are commonly used in automated algorithm selection - the best standalone algorithm (configuration) and the best obtainable sequence of configurations. While the results indicate that the use of the fitness map is not superior on every benchmark problem, it indubitably shows its merit on more hard-to-solve problems. This offers a promising perspective for generalizing to other types of optimization problems and problem domains.

RP-Mod & RP-Crowd: Moderator- and Crowd-Annotated German News Comment Datasets - Assenmacher, Dennis; Niemann, Marco; Müller, Kilian; Seiler, Moritz V.; Riehle, Dennis M.; Trautmann, Heike (Proceedings of the Neural Information Processing Systems Track on Datasets and Benchmarks 1 (NeurIPS Datasets and Benchmarks 2021))
Abuse and hate are penetrating social media and many comment sections of news media companies. These platform providers invest considerable efforts to mod- erate user-generated contributions to prevent losing readers who get appalled by inappropriate texts. This is further enforced by legislative actions, which make non-clearance of these comments a punishable action. While (semi-)automated solutions using Natural Language Processing and advanced Machine Learning techniques are getting increasingly sophisticated, the domain of abusive language detection still struggles as large non-English and well-curated datasets are scarce or not publicly available. With this work, we publish and analyse the largest annotated German abusive language comment datasets to date. In contrast to existing datasets, we achieve a high labelling standard by conducting a thorough crowd-based an- notation study that complements professional moderators’ decisions, which are also included in the dataset. We compare and cross-evaluate the performance of baseline algorithms and state-of-the-art transformer-based language models, which are fine-tuned on our datasets and an existing alternative, showing the usefulness for the community.

Gender and Authority – The Entanglement of Two Concepts in High Medieval Historiography - Foerster, Anne (Geschlecht macht Herrschaft – Interdisziplinäre Studien zu vormoderner Macht und Herrschaft / Gender Power Sovereignty – Interdisciplinary Studies on Premodern Power)

Die Witwenschaft kinderloser Königinnen im Hochmittelalter - Foerster, Anne (Kinderlosigkeit im Mittelalter)

Erklärvideos in der Sprachwissenschaft – Sprache-Bild-Bezüge und ihr Einfluss auf den Lernerfolg (die hochschullehre – Jahrgang 7-2021)

A Database for Research on Detection and Enhancement of Speech Transmitted over HF links - Heitkaemper, Jens; Schmalenstroeer, Joerg; Ion, Valentin; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

How entrepreneur’s leadership behavior and demographics shape applicant attraction to new ventures: the role of stereotypes - Hubner-Benz, Sylvia; Rudic, Biljana; Baum, Matthias (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

An Asia-centric approach to team innovation: Cultural differences in exploration and exploitation behavior - Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli; Tripathi, Neha; Kaschner, Tamara; Le Kong, Xing (Journal of Business Research)
Keywords: Marketing

Introduction - Jacob, Joachim; Süßmann, Johannes (The Reception of Antiquity in the Age of Enlightenment. English Edition ed. by Christina C. Harker. Translated by Duncan Alexander Smart)

Investigating students' processes of noticing and interpreting syntactic language features in word problem solving through eye-tracking - Dröse, Jennifer; Prediger, S.; Neugebauer, P.; Danhier, R. D.; Mertins, B. (International Electronic Journal of Mathematics Education, 16(1), em0625)

Identifying obstacles is not enough for everybody – Differential efficacy of an intervention fostering fifth graders’ comprehension for word problems - Dröse, Jennifer; Prediger, S. (Studies in Educational Evaluation, 68 (100953))

Prokrastination bei Studierenden verringern durch Anwendung eines Ratgebers im Gruppensetting - Korsmeier, Teresa; Bobe, Julia; Klingsieck, Katrin B. (Zeitschrift für Beratung und Studium)

"Welcome to Night Vale" und/mit Derrida: Lernen, mit den Gespenstern zu leben? - Spener, Anna Maria (Literatur und das Böse. Beiträge des 10. Studierendenkongress Komparatistik)

"Meine Trauer war (k)eine Krankheit"? Achronologisches Erzählen einer anhaltenden Trauerstörung in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" - Spener, Anna Maria (Anafora. Zeitschrift für Literaturwissenschaft)

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education - Scheunemann, Anne; Schnettler, Theresa; Bobe, Julia; Fries, Stefan; Grunschel, Carola (European Journal of Psychology of Education)
Abstract Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The present three-wave longitudinal study explored the reciprocal relationships between academic procrastination, study satisfaction, and dropout intentions over one semester. To this end, we used data of N = 326 undergraduate students enrolled in mathematics and law. Our latent cross-lagged panel model replicated existing empirical cross-sectional findings between the variables (i.e., academic procrastination, study satisfaction, and dropout intentions). Regarding the longitudinal relations, as expected, the cross-lagged effects showed that higher dropout intentions significantly related to subsequent higher academic procrastination and lower study satisfaction. Unexpectedly, academic procrastination did not significantly relate to subsequent dropout intentions. Additionally, higher study satisfaction significantly associated with subsequent higher dropout intentions—possibly due to unfulfilled expectations. Further, higher study satisfaction significantly related to subsequent higher procrastination—possibly due to more confidence among satisfied students. Our results broaden the view on dropout intentions as part of the dynamic interplay of student dropout determinants and the need to refine dropout models’ assumptions accordingly. Practically, realistic expectations seem important to reduce dropout intentions. Further, student counselors should have a closer look at the reasons for academic procrastination to develop individual solutions for this dysfunctional behavior.
Keywords: Developmental and Educational Psychology; Education

Digitales Praxissemester - kann das überhaupt gut gehen? - Göddertz, Nina (Care Work in der gesellschaftlichen Transformation. Beschäftigung, Bildung, Fachdidaktik)
Marianne Friese/Rita Braches-Chyrek Einführung Marianne Friese Care Work im Spannungsfeld gesellschaftlicher Transformation. Systemische Widersprüche und Entwicklungsperspektiven Berufliche Bildung und Beschäftigungssysteme Denise Becka und Michaela Evans Wohlfahrtsproduktion und Care im digitalen Wandel: Perspektiven für Beruflichkeit in der Pflege Heidrun Herzberg und Peter Alheit Zur Akzeptanz des Konzepts „Community Nurse" im Land Brandenburg: Eine qualitative Vorstudie Karin Reiber, Jan Braun und Jutta Mohr Berufliche Bildung in der Domäne Pflege zwischen Anforderungen des Beschäftigungssystems und individueller berufsbiografischer Entwicklung Philipp Struck Entwicklungs- und Verbesserungsperspektiven für berufliche (Aus-)Bildungsprozesse im Gesundheitswesen Rita Braches-Chyrek Soziale Arbeit: Ausbildung und Beschäftigung Julia Kastrup und Alexandra Brutzer Hauswirtschaft in Zeiten von Corona - Ergebnisse einer Interviewstudie mit Hauswirtschaftlichen Fachkräften Akademische Bildung und Weiterbildung Anna Bobe, Anke Karber und Tobias Moock Theorie und Praxis in sozialpädagogischen Bildungsgängen - Erste Strukturierungsansätze vielfältiger Verhältnisse Manuela Liebig, Mirjam Chris und Annemarie Marx „Am Ball bleiben" - Sensibilisierung für aktuelle Herausforderungen der sozialpädagogischen Praxis durch Arbeitsanalysen im Lehramtsstudium für berufliche Schulen Anja Walter, Martin Fritzenwanker, Martin Karstädt Von Berufsfeldanalysen zum Unterricht - empirisches Material für die Bildungspraxis im Berufsfeld Gesundheit und Pflege nutzen Nina Göddertz „Digitales Praxissemester - kann das überhaupt gut gehen?" - Reflexionen von Lehramtsstudierenden vor und während des Praxissemesters in Zeiten der Covid-19-Pandemie Stephanie Spanu Systemrelevant(e) ausbilden. Berufliches Lehramt, Fachrichtung Sozialpädagogik und die berufliche Bildung: Der Fachkräftemangel als gesellschaftliche Aufgabe Julia Kastrup, Birgit Peuker, Marie Nölle-Krug und Simon Vollmer Gemeinsam innovativ! - Transformative Themenfelder in der lehramtsbezogenen Ausbildung der beruflichen Fachrichtung Ernährung- und Hauswirtschaft standortübergreifend lehren und lernen Ursula Walkenhorst, Annika Lara Schwarze Digitale Transformation in der Hochschullehre - Chancen und Grenzen für die Gesundheitsberufe Dana Bergmann und Astrid Seltrecht Weiterbildungsordnungsarbeit für Pflegeberufe Claudia Schepers, Johanna Krawietz und Jella Fuchs Kollegiale Beratung für die Kitteltasche
Keywords: Modernisierung personenbezogener Dienstleistungsberufe Aktueller Forschungsstand; Best Practice und Desiderata

A Comparison and Combination of Unsupervised Blind Source Separation Techniques - Boeddeker, Christoph; Rautenberg, Frederik; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised blind source separation methods do not require a training phase and thus cannot suffer from a train-test mismatch, which is a common concern in neural network based source separation. The unsupervised techniques can be categorized in two classes, those building upon the sparsity of speech in the Short-Time Fourier transform domain and those exploiting non-Gaussianity or non-stationarity of the source signals. In this contribution, spatial mixture models which fall in the first category and independent vector analysis (IVA) as a representative of the second category are compared w.r.t. their separation performance and the performance of a downstream speech recognizer on a reverberant dataset of reasonable size. Furthermore, we introduce a serial concatenation of the two, where the result of the mixture model serves as initialization of IVA, which achieves significantly better WER performance than each algorithm individually and even approaches the performance of a much more complex neural network based technique.

Convolutive Transfer Function Invariant SDR Training Criteria for Multi-Channel Reverberant Speech Separation - Boeddeker, Christoph; Zhang, Wangyou; Nakatani, Tomohiro; Kinoshita, Keisuke; Ochiai, Tsubasa; Delcroix, Marc; Kamo, Naoyuki; Qian, Yanmin; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Open Range Pitch Tracking for Carrier Frequency Difference Estimation from HF Transmitted Speech - Schmalenstroeer, Joerg; Heitkaemper, Jens; Ullmann, Joerg; Haeb-Umbach, Reinhold (29th European Signal Processing Conference (EUSIPCO))